(untitled) (Vallis Aurea, 2018)
One of the important tools for selling products is holding shares that stimulate the sales of certain groups of goods. Conducting promotional actions during the crisis period has acquired special significance for both producers and retailers. In the conditions of reduction of real incomes the population searches for ways of economy and more often tries to purchase items with discounts or on special offers. For the consumer, promo becomes a way to reduce the costs of everyday goods, and for suppliers - to increase sales. The article presents the results of research in the field of developing and implementing a policy of discounts. Discount is a key tool to stimulate sales, allowing you to take into account not only the interests of those to whom it is directly provided but also the impact of this step on the entire structure of the relationship in marketing.